Report of the 14th International Scientific Conference on Transformation Processes in Sport “Sports Performance” - Selcuk Akpinar (Journal of Anthropology of Sport and Physical Education, 2017)
The article discusses the highlights of the 14th International Scientific Conference on Transformation Processes in Sport "Sports Performance", which was held in Budva, Montenegro. The event comprised oral and poster sessions. Assistant Professor, Stevo Popovic, Dean of the Faculty for Sport and Physical Education at University of Montenegro, gave one of the opening speeches, as well as Associate Professor Marko Stojanovic, invited speaker from Faculty of Sport and Physical Education at University of Novi Sad, as well as Mr. Dusan Simonovic, president of Montenegrin Olympic Committee, who officially opened the conference.